The cutthroat - Cussler, Clive; Scott, Justin (New York : G.P. Putnam's Sons, 2017)
"The year is 1911. Chief Investigator Isaac Bell of the Van Dorn Detective Agency has had many extraordinary cases before. But none quite like this. Hired to find a young woman named Anna Pape who ran away from home to become an actress, Bell gets a shock when her murdered body turns up instead. Vowing to bring the killer to justice, he begins a manhunt which leads him into increasingly more alarming territory. Anna Pape was not alone in her fate--petite young blond women like Anna are being murdered in cities across America. And the pattern goes beyond the physical resemblance of the victims--there are disturbing familiarities about the killings themselves that send a chill through even a man as experienced with evil as Bell. If he is right about his fears, then he is on the trail of one of the greatest monsters of his time"--
Keywords: Bell, Isaac -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Serial murders -- Fiction; FICTION / Action & Adventure; FICTION / Suspense; FICTION / Historical; Suspense fiction